Analisis Kebutuhan dalam Pengembangan Asesmen Autentik Keterampilan Abad ke-21 untuk Mahasiswa Pendidikan Biologi - Nur Eka Kusuma Hindrasti; Trisna Amelia; Mufida Nofiana (Pedagogi Hayati, 2020)
ABSTRACT. This study aims to analyze the need for the development of authentic 21st century skills assessment instruments for biology education students. This needs analysis research is an early stage of development research consisting of stages 1) need assessment, 2) identification of component scale (literature study), 3) developing and writing items' component, and 4) field testing, validity, and reliability analysis. This descriptive study uses a questionnaire technique to collect data in the form of lecturer and student responses regarding the need for authentic assessment instruments for 21st century skills. Data analysis was performed using simple statistics, namely percentage and also qualitatively. Based on the results of the research, it was found that prospective biology teacher students admitted that lecturers had already assessed 21st century skills, but the lecturers considered that they had not been maximal in assessing 21st century skills because the instruments used were modest, not developed properly (not validated), and have not measured the real skills of students. So that it is important to do research and development of authentic assessment instruments for 21st century skills. ABSTRAK. Penelitian ini bertujuan untuk menganalisis kebutuhan pengembangan instrumen asesmen autentik keterampilan abad ke-21 untuk mahasiswa pendidikan biologi. Penelitian analisis kebutuhan ini merupakan tahapan awal penelitian pengembangan yang terdiri dari tahap 1) need assessment, 2) identification of component scale (studi literatur), 3) developing and writing items’ component, dan 4) field testing, validity, and reliability analysis. Penelitian deskriptif ini menggunakan teknik angket untuk mengumpulkan data berupa respon dosen dan mahasiswa terkait kebutuhan instrumen asesmen autentik keterampilan abad ke-21. Analisis data dilakukan dengan statistik sederhana yaitu persentase dan juga secara kualitatif. Berdasarkan hasil penelitian didapatkan hasil bahwa mahasiswa calon guru biologi mengaku dosen sudah melakukan penilaian keterampilan abad ke-21, namun dosen menganggap belum maksimal dalam menilai keterampilan abad ke-21 karena instrumen yang digunakan dibuat sekedarnya, tidak dikembangkan sebagaimana mestinya (tidak dilvalidasi), dan belum mengukur keterampilan mahasiswa yang sesungguhnya. Sehingga penelitian dan pengembangan instrumen asesmen autentik untuk keterampilan abad ke-21 penting untuk dilakukan.